Decision Support System for Choosing the Best General Practitioner with Additive Ratio Assessment (ARAS) Method - Nursaka Putra; Khairul Imtihan; Partogi Simanjuntak; Mesran Mesran; Hetty Rohayani (The IJICS (International Journal of Informatics and Computer Science), 2023)
A general practitioner is a medical practitioner who focuses on treating sudden or chronic illnesses, and is often considered a first-line doctor. In health services in hospitals, doctors are an important asset. Previously, the selection of the best general practitioner at Bhakti Medan Hospital was done manually, namely through an evaluation of the number of patients cured and the opinions of the nurses who worked with the doctor. However, this method is not effective enough in assessing the professionalism and quality of a doctor. However, determining the best doctor is not easy and requires many criteria, such as communication skills, ability to listen to patients, compliance with the obligations and rights of doctors and patients, rational use of drugs, and adherence to professional ethics. Therefore, a computer-based decision support system is used to assist in selecting the best doctor effectively. Decision support systems are part of a computer-based information system that is used to assist decision making within an organization or company. In this study the authors used the Additive Ratio Assessment (ARAS) method. With the ARAS method the problem of determining the best general practitioner will be easier because the ARAS method in general does a lot of ranking by comparing with other alternatives so as to get the ideal and best results. Based on the results of calculations that have been done previously, in this study it can be concluded that alternative A3 is with a value of 0.1855 on behalf of Dr. Lenny Tampubolon as the best general practitioner at Bhakti General Hospital